Clinical evaluation of serum miR-513a-3p combined with arterial blood gas analysis parameters and lung ultrasound score in neonatal respiratory distress syndrome - Tingting Du; Hui Lei; Jian Dong; Ye Wang; Jun Li (BMC, 2024)
Abstract Background Neonatal respiratory distress syndrome (NRDS) is harmful to neonates and the prognosis is variable, ranging from mild to severe forms. This study aims to evaluate the clinical utility of miR-513a-3p in conjunction with arterial blood gas analysis parameters and lung ultrasound (LUS) score in the context of NRDS. Methods The study included 169 preterm infants, including 106 newborns with NRDS and 63 newborns without NRDS. The relative expression level of miR-513a-3p was detected by quantitative real time polymerase chain reaction (qRT-PCR). Umbilical artery blood gas parameter values and LUS score were recorded, and the clinical significance of miR-513a-3p, umbilical artery blood gas parameter and LUS score in NRDS were evaluated by Receiver Operating Characteristic (ROC) analysis. Results Elevated levels of miR-513a-3p were detected in the serum of NRDS, and higher expression of miR-513a-3p was observed in individuals with poor prognosis. Notably, miR-513a-3p exhibited a significant correlation with the parameters of arterial blood gas analysis and LUS score in NRDS patients. Furthermore, miR-513a-3p was one of the risk factors for poor prognosis in NRDS patients. miR-513a-3p levels combined with umbilical artery blood gas parameters and LUS score has diagnostic value for NRDS and is reliable for its prognosis. Conclusions Elevated levels of miR-513a-3p in neonatal serum served as a useful tool in the combined assessment with umbilical artery blood gas analysis and LUS score to diagnosis and prognosis of NRDS. Consequently, miR-513a-3p may be served as a biomarker for diagnosis and prognosis of NRDS.